Cluster randomised trial of intermittent preventive treatment for malaria in infants in area of high, seasonal transmission in Ghana. Issue 7519 (29th September 2005) - Chandramohan, Daniel; Owusu-Agyei, Seth; Carneiro, Ilona; Awine, Timothy; Amponsa-Achiano, Kwame; Mensah, Nathan; Jaffar, Shabbar; Baiden, Rita; Hodgson, Abraham; Binka, Fred; Greenwood, Brian
Abstract: Objective To evaluate the effects of intermittent preventive treatment for malaria in infants (IPTi) with sulfadoxine-pyrimethamine in an area of intense, seasonal transmission. Design Cluster randomised placebo controlled trial, with 96 clusters allocated randomly to sulfadoxine-pyrimethamine or placebo in blocks of eight. Interventions Children received sulfadoxine-pyrimethamine or placebo and one month of iron supplementation when they received DPT-2, DPT-3, or measles vaccinations and at 12 months of age. Main outcome measures Incidence of malaria and of anaemia determined through passive case detection. Results 89% (1103/1242) of children in the placebo group and 88% (1088/1243) in the IPTi group completed follow-up to 24 months of age. The protective efficacy of IPTi against all episodes of malaria was 24.8% (95% confidence interval 14.3% to 34.0%) up to 15 months of age. IPTi had no protective effect against malaria between 16 and 24 months of age (protective efficacy −4.9%, −21.3% to 9.3%). The incidence of high parasite density malaria (≥ 5000 parasites/μl) was higher in the IPTi group than in the placebo group between 16 and 24 months of age (protective efficacy −19.5%, −39.8% to −2.2%). IPTi reduced hospital admissions with anaemia by 35.1% (10.5% to 52.9%) up to 15 months of age. IPTi had no significant effect on anaemia between 16 and 24 months of age (protective efficacy −6.4%, −76.8% to 35.9%). The relative risk of death up to 15 months of age in the IPTi group was 1.26 (95% confidence interval 0.81 to 1.96; P =0.31), and from 16 to 24 months it was 1.28 (0.77 to 2.14; P =0.35). Conclusions Intermittent preventive treatment for malaria with sulfadoxine-pyrimethamine can reduce malaria and anaemia in infants even in seasonal, high transmission areas, but concern exists about possible rebound in the incidence of malaria in the second year of life.